Methods for enhancing the competence of future english teachers - Ismoilova, Zarnigor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This study investigates methods for developing the lexical competence of future English teachers, a critical component of language proficiency essential for effective teaching. Through a mixed-method approach involving pre- and post-assessment tests, focus groups, and interviews, the study evaluates the effectiveness of various vocabulary enhancement techniques. Results indicate that a combination of contextual learning, technology integration, and direct vocabulary instruction can significantly boost lexical knowledge among teacher trainees. These findings underscore the need for teacher training programs to incorporate diverse lexical teaching methods, preparing teachers to foster vocabulary acquisition in diverse classroom settings.